Avaliação do efeito do cinamaldeído na sepse induzida por Escherichia coli produtora da serinoprotease Pic - FIGUEIREDO, Isabella Fernandes da Silva (2020)
Sepsis is defined as the presence of life-threatening organ dysfunction secondary to the organism's unregulated response to infection. Recently, our group showed that Pic producing-Escherichia coli was responsible for inducing lethal sepsis in mice, causing death within 12 h. Several natural products have been investigated for their bactericidal potential, among these, cinnamaldehyde. The cinnamaldehyde (cinnamic aldehyde or 3-phenyl-2-propenal) is a cyclic terpene alcohol with several biological activities, including antimicrobial activity, antioxidants and anti-apoptotic. Therefore, the aim of this study is to evaluate the activity of cinnamaldehyde in the treatment of animals submitted to sepsis by Pic producing-E. coli. For this, the E. coli F5 was used to evaluate the bactericidal effect. It was incubated with cinnamaldehyde in concentrations ranging from 0.2 to 25 mg/mL, using 96-well plates. Then, they were incubated at 37º for 24 h and after this period Resazurin (0.03%) was used to determine the minimum inhibitory concentration. To evaluate a possible cytotoxic effect, cinnamaldehyde at various concentrations was incubated with Vero cells for 48 h. A total of 100 μL of MTT (3- (4,5- dimethylthiazol-2-yl) -2,5-diphenyltetrazolium bromide) was added and plates incubated for 3 h at 37 °C and 5% CO2. After, Swiss mice from four to eight-week-old weighing on average 25g were used to evaluate the survival. The animal (n = 6 animals / group) were divided ingroups: PBS, Cinnamaldehyde, E. coli F5, prophylactic group and treated group (after infection with E. coli F5). The treated and prophylactic groups received distinct concentrations of cinnamaldehyde (30mg / kg and 60 mg/kg). It was possible to determine that cinnamaldehyde at 6 mg/mL inhibited bacterial growth. In the cytotoxicity assay, none of the cinnamaldehyde concentrations showed toxicity to Vero cells. The survival trial showed that cinnamaldehyde at 60 mg/kg was able to keep 33% of mice alive after infection. In addition, it is evident in the present study that the CNA demonstrates potential anti-inflammatory actions and immunomodulators that can help control and balance these sepsis events. The decrease / maintenance of some cell types such as lymphocytes at the infection site, the reduction of NO, and the regulation of some cytokines can contribute positively to the control of this syndrome.